Anthocyanin biosynthetic pathway switched by metalloregulator PbrR to enable a biosensor for the detection of lead toxicity - Guo, Yan; Huang, Zhen-lie; Zhu, De-long; Hu, Shun-yu; Li, Han; Hui, Chang-ye (Frontiers in Microbiology, 2022)
Environmental lead pollution mainly caused by previous anthropogenic activities continuously threatens human health. The determination of bioavailable lead is of great significance to predict its ecological risk. Bacterial biosensors using visual pigments as output signals have been demonstrated to have great potential in developing minimal-equipment biosensors for environmental pollutant detection. In this study, the biosynthesis pathway of anthocyanin was heterogeneously reconstructed under the control of the PbrR-based Pb(II) sensory element in Escherichia coli. The resultant metabolic engineered biosensor with colored anthocyanin derivatives as the visual signals selectively responded to concentrations as low as 0.012 μM Pb(II), which is lower than the detection limit of traditional fluorescent protein-based biosensors. A good linear dose-response pattern in a wide Pb(II) concentration range (0.012-3.125 μM) was observed. The color deepening of culture was recognized to the naked eye in Pb(II) concentrations ranging from 0 to 200 μM. Importantly, the response of metabolic engineered biosensors toward Pb(II) was not significantly interfered with by organic and inorganic ingredients in environmental water samples. Our findings show that the metabolic engineering of natural colorants has great potential in developing visual, sensitive, and low-cost bacterial biosensors for the detection and determination of pollutant heavy metals.